Emergency Nurse Practitioner Core Educational Content. (April 2017) - Wilbeck, Jennifer; Roberts, Eric; Rudy, Susanna
Abstract : Increasing numbers of patients are presenting to national emergency departments (EDs). This is occurring simultaneously with reductions in providers along with ED closures, creating a significant gap in emergency care. According to the advanced practice registered nurse consensus model, specialty-specific knowledge and practice build upon generalist nurse practitioner (NP) population foci. Although the National Organization of Nurse Practitioner Faculties provides guidelines for educational programs at the NP population level, determination of core specialty knowledge lies with specialty organizations. Emergency nurse practitioners (ENPs) require additional specialty-specific education to manage patients spanning age and acuity continuums. Although certification mechanisms are now in place to recognize NP specialty knowledge, a nationally standardized curriculum remains to be proposed. This article proposes core educational content for ENP specialty education; the utility of this content may serve as the foundation for the development of standardized ENP academic and postgraduate fellowship programs.